Menimbang Model Pengujian Keputusan Pejabat Publik oleh Mahkamah Konstitusi Republik Indonesia (Studi Perbandingan Indonesia dan Korea Selatan) - Yunita Nurwulantari; Anna Erliyana (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Testing public officials decision in Indonesia, which has been the authority of the State Administrative Court (PTUN) should be done through a constitutional complaint mechanism, written under the authority of the Constitutional Court of the Republic of Indonesia (MKRI). This is due to all public officials have the potential to perform acts that violate or harm the constitutional rights of citizens as guaranteed in the 1945 Constitution (UUD 1945). This additional authority to examine and decide cases of constitutional complaints should be possible in the framework of carrying out the functions of the Constitutional Court as the guardian of the constitution as implemented in countries that apply the principle of constitutional supremacy, one of which is as applied in the Constitutional Court of The South Korea. Even though South Korea has an administrative court which also has the authority to examine the decision of public officials, South Korea still open space for its citizens to file constitutional complaint in Constitutional Court of South Korea when there is a public official decision that harm and violating the constitutional rights of the citizens that have been guaranteed in constitution. Thus, when all legal remedy for violations of constitutional rights as a result of the issuance of public official decision has been exhausted, but violations still occur, then this constitutional complaint mechanism into the need to provides maximum protection and respect the constitutional rights of citizens. Therefore, the additional authority to examine and decide constitutional complaint can not be separated from the authority of the Constitutional Court.